Quality Assessment Of Public Pipe Borne Water Supply And It’s Implications For Public Safety In Abuja Metropolis, Nigeria - Onyenekwe P.C, Bindir Umar Buba, Nwaedozie Isaac, .Madueke, Abdulqadir Ibrahim, (International Journal of Scientific Research and Management (IJSRM), 2014)
Public pipe borne water quality assessment of Abuja Metropolis was investigated for two years with the aimto assess its public health safety. Representative water samples were collected from each of the five majordistricts both in rainy and dry seasons according to standard methods and procedures and screened forcolour, Turbidity, PH, residual chlorine, total coli forms and Escherichia Coli within the period of study.The results indicated as follows: colour (8.10±0.55-10.01±0.97Pt.Co) ,turbidity( 1.42±0.43- 2.69±0.41NUT) , pH (6.5±0.22-7.23±0.87), residual chlorine (0.09±0.03-0.12±0.03mg/l-1),total coli forms(0±0-10.30±1.78cfu/100ml ) and E.Coli (0±0-0±0cfu/100ml) .The study found that parameters were within therespective guideline values recommended by the WHO against each parameter for safe drinking waterquality accept for residual chlorine and particularly during the raining season. The study also observed thatthe so also the PH of the water supply was in the majority cases across the districts were below 7.0The study therefore concluded that the public water supply in Abuja Metropolis may not constitute anysignificant health risk upon consumption based on the established empirical scientific evidence andrecommended improvement in the chlorine dosing threshold particularly during rainy seasons as well asprompt maintenance of leakages and faults along water distribution system.